Soil microbial community and influencing factors of different vegetation restoration types in a typical agricultural pastoral ecotone - Huang, Pei; Shi, Hanyu; Jiang, Lina; Zhu, Duoping; Zhou, Zefeng; Hou, Zhenhong; Ma, Xingyu (Frontiers in Microbiology, 2025)
Microbial network complexity is an important indicator for assessing the effectiveness of vegetation restoration. However, the response of the microbial network complexity of bacteria and fungi to different vegetation restoration types is unclear. Therefore, in this study, we selected four vegetation restoration types (Pinus sylvestris var. mongholica, Larix principis- rupprechtii, Populus tomentosa, and Ulmus pumila), while selected the nature grassland as a control, in the Zhangjiakou Tunken Forest Farm, which is a typical agricultural pastoral ecotone in northern China, to investigate the response of soil microbial diversity and network complexity to different vegetation restoration types. Our result showed that the bacterial Shannon and Chao indices of P. sylvestris var. mongholica were significantly 7.77 and 22.39% higher than those of grassland in the 20–40 cm soil layer, respectively. The fungal Chao indices of U. pumila were significantly 85.70 and 146.86% higher than those of grassland in the 20–40 cm and 40–60 cm soil layer, respectively. Compared to natural grassland, soil microbial networks became more complex in plantation forests restoration types (P. sylvestris var. mongholica, L. principis- rupprechtii, P. tomentosa, and U. pumila). Microbial network complexity increased with soil carbon and nitrogen. P. tomentosa is suitable for planting in the agricultural pastoral ecotone of Zhangjiakou, because of its high soil carbon, nitrogen and microbial network complexity. Bacterial community composition was found to be closely related to soil organic carbon (SOC), total nitrogen (TN), while that of fungi was closely related to SOC, clay and silt content. This improvement in microbial complexity enhances the ecological service function of the agricultural pastoral ecotone. These findings offer theoretical basis and technical support for the vegetation restoration of ecologically fragile areas in agricultural pastoral ecotone.